2012
DOI: 10.1002/pits.21658
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly Productivity and Impact of School Psychology Faculty in APA‐Accredited Programs

Abstract: The primary objective of this study was to conduct a normative assessment of the research productivity and scholarly impact of tenured and tenure‐track faculty in school psychology programs accredited by the American Psychological Association (APA). Using the PsycINFO database, productivity and impact were examined for the field as a whole and by faculty rank and gender between 2005 and 2009. Results of our study reflected considerable variability in scholarly impact and productivity. For example, on average, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…The most recent survey of publications found that the number of papers was positively skewed with many faculty publishing few papers and a few faculty publishing many papers (Grapin et al, 2013). A similar skewed distribution was found for the number of citations.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The most recent survey of publications found that the number of papers was positively skewed with many faculty publishing few papers and a few faculty publishing many papers (Grapin et al, 2013). A similar skewed distribution was found for the number of citations.…”
Section: Discussionmentioning
confidence: 68%
“…1 and 3). Grapin et al (2013) did not consider years of experience nor rank and found significant differences between male and female school psychology faculty members in favor of males, but the amount of variance explained by sex differences was small (≈2-4%). Other studies of academic psychologists have found that seniority or rank accounted for most of the difference in male-female research productivity (Duffy et al, 2011;Nosek et al, 2010).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Firstly, studies of factors that contribute to research productivity have intensified within academic disciplines and across countries with increasing emphasis on how it should be developed (e.g. Serenko and Bontis 2004;Grapin et al 2013). Secondly, and relatedly, there has been an emphasis on the contribution of doctoral students to research productivity (Boud and Lee 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Scholarly productivity is one of the most critical considerations of success for faculty in many universities, with an increased focus not only on the quantity of peer‐reviewed publications but the quality of those publications (Joy, ; McCleary, Aspiranti, & Henze, ). Infrequent publication or a majority of publications located in low‐quality journals can lead to a denial of tenure and decreased professional opportunities (Grapin, Kranzler, & Daley, ; Shaw & Glaser, ). Prolific scholars are often among the most widely recognized and well‐respected in their field, thereby demonstrating the effect that scholarship has on academic status, reputation, or prestige.…”
mentioning
confidence: 99%